POTRET WANITA DALAM CERMIN KEINDAHAN KARYA SASTRA - Ika Selviana (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
A literary work is always identical with the word of beauty. It is because the selected words in creating the literature are the connotative words by considering the aesthetics existed in the sound and diction. At present, women as the symbol of beauty and have problematic issues of life are existed in the various literatures both in the form of short story and novel which narrate more about the women’s problems in their live. However, behind the authors’ fluctuations who want to express a variety difficulties and persecutions of women as beings who want to be equal with men, so the literary works with sexuality genre showing the feminine side openly once taboo in the world of authorship arise. This study seeks to highlight the literary works of women authors; Djenar Maesa Ayu is one of the authors who displays the works of feminism. Her work entitled “Cerita Pendek Tentang Cerita Cinta Pendek” for the adult readers was very openly about sexuality, abusing, and persecution of women. So, the researcher wanted to know about the style of language used, beauty, content of the story, and how Djenar photographing the reality of women’s lives through the study of stylistic and aesthetics.